Pelaksanaan Program Rumah Belajar bagi Anak Gampong Meunasah Papeun untuk Meningkatkan Motivasi Belajar dengan Berbasis Hidden Curriculum - Ridha Aulia; Agam Muhammad Rizki; Rosa Zulfikhar; Dwi Surti Junida; Inayatul Mutmainnah (I-Com: Indonesian Community Journal, 2024)
Program Rumah Belajar with a Hidden Curriculum Basis is a program implemented to increase the learning motivation of children in Gampong Meunasah Papeun. This program was implemented because there was a situation where the learning motivation of students in the gampong was said to be low by the parents and guardians. This program is implemented in four stages including: Observation, Licensing, Implementation and Closing. In conclusion, the Program Rumah Belajar with a Hidden Curriculum Basis has been able to increase the learning motivation of Meunasah Papeun village children. This kind of program must be facilitated and must be implemented continuously to make children and students have high enthusiasm and motivation to learn. Thus, educational goals are achieved.